CASUS BELLI PROBLEM IN PUBLICISTIC WRITINGS OF VINCAS KUDIRKA - VAIŠNYS, ANDRIUS (Knygotyra, 2015)
The article explores a still topical issue concerning publicistic writings of Vincas Kudirka, a leader of the 19th century political struggle of Lithuanians and a publicist, characterized by him as casus belli, i. e. a pretext to “instigate war” accusing him of an attack against a certain social stratum. The author of the article presents a fresh look at the most sensitive three themes which don’t stop provoking public resonance produced by V. Kudirka’s diary Bells of Fatherland (which now can be equated with evil), taking into consideration the contents of the publication: the conduct of the Catholic Church, the enterprise of the Jewish community, and the separability of Lithuanian and Polish cultures.The volume of the study of these themes is small, i. e. from 2.6 to 7 per cent in comparison with the amount of the published and commented facts, in the whole work (385 problematic episodes). However, it was not only at the time of its publication that Bells of Fatherland provoked (particularly the criticism of priests). Even today, due to the presentation style of the mentioned themes, V. Kudirka is sometimes referred to as an anti-Semite, an atheist and by other characteristics. The article reviews the cultural and literary sources as well as the circumstances (particularly his life in Warsaw) which exerted influence on Kudirka’s world perception. The author of the article is of the opinion that today’s anti-Semitic conception should not be employed in respect of the personality of V. Kudirka since the publicist, as a satirist and critic, presented 19th century problems, social conflicts and didn’t participate in any organization marked by anti-Semitic or anticlerical features. He was concerned with restraint rights of the Lithuanian nation in the Russian empire. The author is convinced that the attempts to employ V. Kudirka’s extracts from the 19th century context in today’s anti-Semitic publications are a dishonest and vulgar action.
Keywords: ...